2016
DOI: 10.1037/lhb0000201
|View full text |Cite
|
Sign up to set email alerts
|

Juror sensitivity to false confession risk factors: Dispositional vs. situational attributions for a confession.

Abstract: Research on jurors' perceptions of confession evidence suggests that jurors may not be sensitive to factors that can influence the reliability of a confession. Jurors' decisions tend not to be influenced by situational pressures to confess, which suggests that jurors commit the correspondence bias when evaluating a confession. One method to potentially increase sensitivity and counteract the correspondence bias is by highlighting a motivation other than guilt for the defendant's confession. We conducted 3 expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 67 publications
20
62
1
Order By: Relevance
“…Several studies have found that jurors discounted confessions obtained via psychological manipulation (e.g., Horgan, Russano, Meissner, & Evans, 2012;Woestehoff & Meissner, 2016), while others suggest that jurors do not see these techniques as problematic (Leo & Liu, 2009) and are no less likely to convict when they are used (Kassin & McNall, 1991). Because our study depicted the exoneree's interrogation as either overtly or not-at-all coercive, we cannot say how jurors would react to an exoneree who confessed in response to subtler forms of coercion.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Several studies have found that jurors discounted confessions obtained via psychological manipulation (e.g., Horgan, Russano, Meissner, & Evans, 2012;Woestehoff & Meissner, 2016), while others suggest that jurors do not see these techniques as problematic (Leo & Liu, 2009) and are no less likely to convict when they are used (Kassin & McNall, 1991). Because our study depicted the exoneree's interrogation as either overtly or not-at-all coercive, we cannot say how jurors would react to an exoneree who confessed in response to subtler forms of coercion.…”
Section: Discussionmentioning
confidence: 69%
“…Although overt threats and intimidation are sometimes present in real‐world interrogations (e.g., Cleary & Warner, ; Kassin et al, ; Leo, ), interrogators are typically trained to elicit confessions via subtler psychological manipulation (i.e., the Reid Technique; Inbau, Reid, Buckley, & Jayne, ), which jurors may not see as coercive. Several studies have found that jurors discounted confessions obtained via psychological manipulation (e.g., Horgan, Russano, Meissner, & Evans, ; Woestehoff & Meissner, ), while others suggest that jurors do not see these techniques as problematic (Leo & Liu, ) and are no less likely to convict when they are used (Kassin & McNall, ). Because our study depicted the exoneree's interrogation as either overtly or not‐at‐all coercive, we cannot say how jurors would react to an exoneree who confessed in response to subtler forms of coercion.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases (besides from in one study, which was unclear about the type of question asked), these questions were Likert‐scale questions, requiring participants to select the response option specified in the question (e.g., “strongly agree,” based on Oppenheimer et al, 2009). Nine studies asked just one attention check question, two studies asked three attention check questions, and Woestehoff & Meissner (2016) did not specify how many attention check questions were included in their three studies. Exclusions based of failed attention check questions ranged from .7% of the total sample (Woestehoff and Meissner, 2016: study 1) to 14% of the total sample (Teitcher & Scurich, 2017: study 3).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies asked just one attention check question, two studies asked three attention check questions, and Woestehoff & Meissner (2016) did not specify how many attention check questions were included in their three studies. Exclusions based of failed attention check questions ranged from .7% of the total sample (Woestehoff and Meissner, 2016: study 1) to 14% of the total sample (Teitcher & Scurich, 2017: study 3). In Giffin and Lombrozo's (2016) studies, up to 17% of the sample was excluded, but given that they asked a combination of attention and general memory questions, it is unclear what portion of their exclusions were attributable to the attention checks.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as the seriousness of the crime increases (e.g. homicide), people find it even harder to understand and accept that an individual would falsely confess to the crime (Drake, 2011;Henkel, Coffman, & Dailey, 2008;Leo & Liu, 2009;Woestehoff & Meissner, 2016). To date, however, the Innocence Project (2006) states that more than 220 individuals have been exonerated and released from prison, after post-conviction DNA testing.…”
mentioning
confidence: 99%